Humidity‐dependant compression properties of graphene oxide foams prepared by freeze‐drying technique. (1st February 2013) - Ming, Renhu; Ding, Yanhuai; Chang, Feihu; He, Xing; Feng, Jiqiang; Wang, Chengfu; Zhang, Ping
Abstract : Microstructured graphene oxide (GO) foams were prepared by a freeze‐drying technique. The morphology, structure and compression properties of the GO foams were characterised by X‐ray diffraction, Fourier transform infrared spectroscopy, atomic force microscopy and an electronic universal‐testing machine. The unique pore structure made the GO foam easy to recover after compression. Furthermore, the compression properties of GO foam exhibited a humidity sensitivity, and the compressive strength was reduced by decreasing the relative humidity.